Deposition of copper sulfide films on polyamide surface - Petrasauskiene Neringa; Paluckiene Edita; Alaburdaite Rasa; Gilić Martina (Science of Sintering, 2022)
In this paper, we present a novel and low - cost method for preparing copper sulfide films on polyamide. Non-treated as well as pre-treated PA6 films by 3 different methods (in boiled water; in NaOH solution; in boiled water and then in NaOH solution) were used for the formation of Cu2S layers by the sorption-diffusion method. Molten sulfur has been used as a sulfurization agent. The XRD, FTIR, and UV-VIS methods were used to characterize the structural, optical, and electrical properties of samples and to track changes in samples after each treatment stage. The sheet resistance of Cu2S layers depends on the pre-treatment method and varied from 7 kΩ/sq to 6 MΩ/sq. The optical band gaps (Eg) for direct and indirect transitions are determined to be 2.61-2.67 eV and 1.40-1.44 eV, respectively. Furthermore, the optical constants n, k, and σ are determined from UV-VIS measurements.